2019
DOI: 10.1002/anie.201906063
|View full text |Cite
|
Sign up to set email alerts
|

Arylation of Axially Chiral Phosphorothioate Salts by Dinuclear PdI Catalysis

Abstract: S‐aryl phosphorothioates are privileged motifs in pharmaceuticals, agrochemicals, and catalysts; yet, the challenge of devising a straightforward synthetic route to enantioenriched S‐aryl phosphorothioates has remained unsolved to date. We demonstrate herein the first direct C−SP(=O)(OR′)(OR′′) coupling of diverse and chiral phosphorothioate salts with aryl iodides, enabled by an air‐ and moisture‐stable PdI dimer. Our mechanistic and computational data suggest distinct dinuclear PdI catalysis to be operative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 80 publications
1
36
0
Order By: Relevance
“…18 Schoenebeck has recently shown that Ar-S-P(O)(OR) 2 can also be easily accessed via palladium catalysis from the parent aryl iodides. 19 Additionally, Gooen and Tang have developed protocols which enable the synthesis of aryl phosphorothiolates through S E Ar from electron-rich arenes or via Cu-catalyzed/mediated cross-coupling from the corresponding diazonium salt or boronic acid. 20 The possibility to access these compounds from a myriad of diverse starting materials further supports the consideration of Ar-S-P(O)(OR) 2 as convergent linchpin reagents.…”
Section: Special Topic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…18 Schoenebeck has recently shown that Ar-S-P(O)(OR) 2 can also be easily accessed via palladium catalysis from the parent aryl iodides. 19 Additionally, Gooen and Tang have developed protocols which enable the synthesis of aryl phosphorothiolates through S E Ar from electron-rich arenes or via Cu-catalyzed/mediated cross-coupling from the corresponding diazonium salt or boronic acid. 20 The possibility to access these compounds from a myriad of diverse starting materials further supports the consideration of Ar-S-P(O)(OR) 2 as convergent linchpin reagents.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…As noticed in previous works, Ar-SF 4 Cl compounds are highly reactive and their isolation is extremely challenging. Therefore, the yields were calculated by 19 F NMR spectroscopy by using an internal standard.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“… Heteroatom bond formation via dinuclear catalysis using thiolates or selenolates (top) [35] and phosphorothioates (bottom) [36] …”
Section: Applications In Cross‐couplingmentioning
confidence: 99%
“…Phosphorothioates ( − SP(=O)(OR) 2 ) were also demonstrated to be suitable coupling partners in Pd I ‐mediated bond formation, which enabled the first C−SP(=O)(OR) 2 coupling of aryl halides (Figure 8). By contrast, traditional Pd 0 /Pd II catalysis failed to deliver the phosphorothioate cross‐coupling product as a consequence of a prohibitively high activation barrier for the reductive elimination from the key Pd II intermediate and a lack of driving force [36] . Stoichiometric experiments with Pd I dimer 2 and 31 P NMR analysis clearly indicated the formation of a new Pd I dimer, demonstrating the competence of phosphorothioates to stabilize the Pd I scaffold and the altered driving force for exchange at Pd I .…”
Section: Applications In Cross‐couplingmentioning
confidence: 99%
“…[11] The preparation of these compounds using PÀ S bond forming chemistry has been the subject of extensive study in recent years. Metal-catalysed coupling reactions employing copper, [12] rhodium, [13] palladium, [14] iron [15] and iridium [16] catalysts have been developed. Unfortunately, these routes are largely restricted to S-aryl products and are often low yielding or incompatible with S-alkyl targets.…”
mentioning
confidence: 99%